Study on user influence analysis via regional user interaction model in online social networks - Nan WANG; dong SUNQin; dong ZHOUYa; qin WANGHan; sheng SUILian (Tongxin xuebao)
Conventional user influence researches do not accurate reflect the real interaction pattern between different users in online social networks. In order to solve this problem,a user influence evaluation method based on regional user interaction model has been proposed. The regional user interaction model can illustrate the real online social network user interaction pattern between users with different distance by the influence transfer effect. The method calculates the direct influence and the indirect influence of each user in online social networks and identifies the influential users and zombie users. Experiments are based on the real data of Sina Weibo and RenRen online social networks and the results show that compared with the existing methods the method has better accuracy and efficiency for the infl tial user and zombie us-er identification.